Expansão e interiorização das Universidades Federais: uma Análise do Processo de Implementação do Campus do Litoral Norte da Universidade Federal da Paraíba - Nascimento, Francivaldo dos Santos (2013)
In 2004, the federal government began a process of federal public universities expansion. With the Expand Program , new universities were established, colleges were transformed into universities, in addition to creating new campuses through the process of internalization, aiming to reach people who are distant from large urban centers and who need to access the higher education. Given this context of expansion, since 2005 this institution resumed its process of internalization through the creation of the Campus IV (North Coast), located in the cities of Rio Tinto and Mamanguape. This paper aims to analyze the implementation process of the North Coast Campus. The theoretical framework presented the following topics: public policies, concepts, types, and its cycle and stage of implementation, in which was presented the implementation model of Smith; public policies for higher education in Fernando Henrique Cardoso and Lula governments, and finally, the public university. The methodological approach used was the qualitative research, classified as descriptive, and it was used the case study method. Data were collected from primary data collected through interviews with nine people, professors and technical and administrative staff, who participated directly in the implementation process. Secondary data were also used, such as institutional documents, and newspaper articles published in the local press. In the data analysis, content analysis was used through thematic and documentary categories. The data allowed us to analyze the process of implementing in the following perspectives: by the institutional perspective, the political and institutional aspects; by the material perspective, the technical and administrative aspects; and by the procedural perspective, the relationship with the society. The survey results revealed that the process of implementing the North Coast Campus had political influence, mainly in the choice of the cities that would receive the campus; a strategic action of enormous educational, social and economic relevance; lack of proper planning; many difficulties in the implementation, particularly in the building process, but there was a great dialogue with the community. The campus has faced the consolidating process of its academic structure, reaching the goals that justified its creation. The implementation was revealed, on one hand, as a process permeated by enormous problems and conflicts that have caused many difficulties for the entire academic community, but on the other hand, the initiatives that could, for example through actions such as preparatory university courses created in cities nearby the North Coast Campus, attract a significant number of students who have been successful in the selection process and have joined the campus. It is possible to conclude that, while conducting a process of implementation of public policy, it is necessary to plan all the steps to take them quite carefully, so problems can be minimized or even avoided, considered critical in this step of public policy, but of main importance to achieve the goals set by the policy. By adverse situations encountered during the implementation of the North Coast Campus, for UFPB, is learning this internalization, showing the need to have an experienced team to manage the entire implementation process, seek the commitment of institutional partners, while not may waive the participation of the community.